Interprofessional education during experiential learning placements for student pharmacists in Scotland. Exploring current support provision and stakeholder views. (30th November 2022) - Depasquale, C; Cunningham, S; Boyter, A; Jacob, S A; Power, A; Portlock, J; Addison, B
Abstract: Introduction: Increasing global awareness that interprofessional team working is essential within modern healthcare systems has led to regulatory bodies mandating the inclusion of interprofessional education (IPE) within undergraduate curricula. The General Pharmaceutical Council specifies in the 2021 initial education and training standards the requirement for an interprofessional learning plan in which "IPE must mirror practice". 1 Pharmacy educators are intensifying their efforts to ensure student pharmacists are presented with opportunities to develop collaborative competencies. Curricular development and implementation initiatives must explore structures and processes to ensure that experiential learning (EL) environments are conducive to supporting student pharmacists' interprofessional learning. Aim: To explore structures and processes needed to support effective planned and unplanned IPE during EL placements for student pharmacists. Methods: A mixed methods approach underpinned by the Biggs 3P theoretical framework was adopted. 2 This included (1) A document analysis reviewing resources including student pharmacist/EL facilitator university handbooks and NHS Education for Scotland Preparation for Facilitating Experiential Learning (PFEL) training - a mandatory requirement for all EL facilitators hosting student pharmacists on placement in Scotland. (2) A pre-piloted online survey distributed to EL facilitators. Survey development, guided by the Interprofessional Facilitation Scale, aimed to encourage EL facilitators to self-evaluate their own IPE facilitation skills. 3 The final survey tool included ten items with responses rated on a 4-point Likert scale (Poor, Fair, Good and Excellent) and a demographic section (3) Online semi-structured focus groups/dyadic interviews conducted with six EL facilitators, four practice educators and two academic staff were recorded and transcribed. Descriptive statistics were employed for quantitative data generated from the survey tool; for qualitative data content analysis was applied to develop emerging themes. Ethical approval was granted (S292) from the School of Pharmacy and Life Sciences Ethics Review Committee at Robert Gordon University. Results: (1) The document analysis concluded that although the resources reviewed could not be specifically classed as training to support IPE, data collected provided context to EL placements and the training and pre-activities that student pharmacists and EL facilitators complete. Three main themes emerged: "Lack of specific IPE training focus", "Varied terminology", "Lack of IPE pre-learning activities". (2) The survey was completed by ninety EL facilitators working in various practice settings: hospital 41.1% (n=37); primary care 25.6% (n=23); community 21.1% (n=19); academia 2.2% (n=2); other 8.9% (n=8). Survey responses indicated that 51.1% (n=46) and 42.2% (n=38) of respondents rated their ability to role model positive interactions with other healthcare professionals as good and excellent. However, responses to items relating more specifically to IPE facilitation skills indicated a lower confidence level. (3) Initial themes emerging from focus groups/dyadic interviews include "Profession-related perceptions of IPE", "Factors influencing IPE delivery and student learning", "Factors influencing future developments". Discussion/Conclusion: This exploratory study has provided valuable insight into multifactorial aspects affecting IPE during EL placements; this will be used to guide future development of IPE initiatives. One limitation is that student pharmacists were not included in this study; the next phase of this research programme will explore student pharmacists' perceptions of IPE in EL. References: 1. General Pharmaceutical Council. Standards for the initial education and training of pharmacists. [homepage on the Internet]. London: GPhC; 2021. Available from: https://www.pharmacyregulation.org/sites/default/files/document/standards-for-the-initial-education-and-training-of-pharmacists-january-2021.pdf 2. Biggs, J.B. From Theory to Practice: A Cognitive Systems Approach. High Educ Res Dev, 1993, 12(1), 73-85 3. Sargeant J., Hill T., Breau L. Development and testing of a scale to assess interprofessional education (IPE) facilitation skills. J Cont Educ Health Prof, 2010, 30(2), 126-131